Edukasi Kesehatan Reproduksi Menggunakan Media Booklet terhadap Peningkatan Pengetahuan Tentang Infeksi Menular Seksual Pada Wanita Usia Subur - Wulan Novika Ambarsari; Atira Atira; Assyani Nursafitri (Health Idea, 2023)
Sexually Transmitted Infections (STIs) are one of the public health problems in West Java in 2017, namely 1,877 cases. The incidence of STIs in women of childbearing age based on laboratory results from the Cimahi City Health Service is 462 people who contracted STIs in 2022. The causes of this incident include the low level of knowledge possessed by women of childbearing age. One method that is thought to be able to increase reproductive health knowledge about sexual infections in women of childbearing age is providing reproductive health education using Booklet Media. The aim of this research is to determine the effect of reproductive health education using booklet media on the level of knowledge about sexually transmitted infections in women of childbearing age. The research method uses pre-experimental designs with a one group pretest posttest design. The research sample was 60 respondents with a total sampling technique. Test knowledge data analysis using Marginal Homogeneity. The research results show that there is an influence of reproductive health education using booklet media on the level of knowledge about sexually transmitted infections in women of childbearing age with a value of p = 0.000 < α = 0.05, so Ho is rejected and H1 is accepted. Suggestion: Health education using booklet media can be applied in order to increase public knowledge so that people can avoid sexually transmitted infections, especially women of childbearing age so that they are free from STIs.